2022
DOI: 10.18311/jnr/2022/28740
|View full text |Cite
|
Sign up to set email alerts
|

<i>Bauhinia variegata</i> Bark Extract: Assessment of its Anti-proliferative and Apoptotic Activities on A549 and H460 Lung Cancer Cell Lines

Abstract: The hunt for novel anticancer drugs with minimal side effects continues. This study strengthens the claim by providing biochemical evidences of anticancer activities of<em> Bauhinia variegata</em> bark extracts on lung carcinoma cells (A549 and H460). Bark extracts of <em>Bauhinia variegata</em> were prepared by different solvents using Soxhlet apparatus and tested for their antioxidant potential by DPPH assay. The lung cancer cell lines were treated with <em>Bauhinia variegata<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
1
Order By: Relevance
“…Colony formation and cell migration are important processes for the proliferation of cancer cells indicative of cancer metastasis and are lethal to a patient's life. A study on lung carcinoma (H460) cells observed that chloroform bark extract of B. variegata (CBE) significantly inhibited colony formation at a 2 mg/mL concentration, 64 while our study showed a significant reduction in viability of both tested cancer cells at a relatively lower dose of plant extract. Moreover, our study revealed that cell migration was significantly reduced in response to the plant extracts in both cell lines.…”
Section: Discussioncontrasting
confidence: 56%
“…Colony formation and cell migration are important processes for the proliferation of cancer cells indicative of cancer metastasis and are lethal to a patient's life. A study on lung carcinoma (H460) cells observed that chloroform bark extract of B. variegata (CBE) significantly inhibited colony formation at a 2 mg/mL concentration, 64 while our study showed a significant reduction in viability of both tested cancer cells at a relatively lower dose of plant extract. Moreover, our study revealed that cell migration was significantly reduced in response to the plant extracts in both cell lines.…”
Section: Discussioncontrasting
confidence: 56%